The Efficacy of Virtual Physical Education and Its Contribution to Raising Learners' Interest and Engagement Levels - Mdhlalose, Dickson (CV Rezki Media, 2024)
Background: Schools are reluctant to adapt physical education to virtual as it would be challenging to do physical education via virtual learning. Objectives: This study aimed to assess the contemporary efficacy of virtual physical education and its contribution to raising learners' interest and engagement levels. Methods: This study employed an exploratory research design. The content was compiled using various printed and electronic textbooks, encyclopedias, reference materials, scholarly publications, and dissertations. Subsequently, the author assessed the multiple sources to ascertain the data's caliber. Results: Conventional education is obsolete; thus, schools should adopt virtual physical education due to its positive outcomes in education regarding learners' performance by increasing learners' interest and engagement. Conclusion: A properly planned and well-implemented virtual physical education, well-trained and experienced educators, well-guided learners, proper infrastructure, and supporting resources result in learners being interested and engaged, thus leading virtual physical education to success. This study bridges the gap between virtual physical education and learners' interest and engagement, adding to the existing corpus of information concerning virtual physical education.